2004
DOI: 10.1111/j.1572-0241.2004.40069.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Lamivudine Administration Prevents Exacerbation of Liver Damage in HBe Antigen Positive Patients with Hepatocellular Carcinoma Undergoing Transhepatic Arterial Infusion Chemotherapy

Abstract: These results indicate that prophylactic lamivudine administration reduces HBV-DNA levels and prevents exacerbation of liver damage throughout the period of chemotherapy in HBe antigen positive patients with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 34 publications
1
50
0
1
Order By: Relevance
“…This finding is in agreement with the findings of a retrospective study in which lamivudine prophylaxis prevented a deterioration in hepatic functions in HBeAg-positive HCC patients undergoing intraarterial infusion chemotherapy. 21 The beneficial effects of preemptive therapy on the severity of hepatitis most probably result from an elimination of any potential risk arising from viral reactivation. Whether preemptive antiviral therapy would reduce hepatic adverse events during TACL irrespective of viral reactivation remains an issue that should be evaluated further.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the findings of a retrospective study in which lamivudine prophylaxis prevented a deterioration in hepatic functions in HBeAg-positive HCC patients undergoing intraarterial infusion chemotherapy. 21 The beneficial effects of preemptive therapy on the severity of hepatitis most probably result from an elimination of any potential risk arising from viral reactivation. Whether preemptive antiviral therapy would reduce hepatic adverse events during TACL irrespective of viral reactivation remains an issue that should be evaluated further.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all these patients had intense marrow suppression with a drastic reduction of white cell count, and the rebound of the white cell with immune recovery correlates with the initiation of liver damages [56]. Severe hepatitis due to HBV reactivation has also been reported in HBV-infected patients treated with chemotherapy for other malignancies such as breast cancer [10][11][12], hepatocellular carcinoma [18,57,58], small-cell lung cancer [59], and nasopharyngeal cancer [60]. The relative lack of report in other type of malignancy is probably related to their lower incidence in HBV endemic area, such as the Asia-Pacific region.…”
Section: Chemotherapy or Immunosuppressive Therapy Related To Hbv Reamentioning
confidence: 99%
“…On the other hand, prolonged therapy with nucleos(t)ide analogues is associated with an increased likelihood of developing lamivudine-resistant mutants. Hence, most cancer centers would aim at discontinuing or withdrawing preemptive lamivudine as soon as possible to limit the duration of antiviral therapy [57,85,86,[111][112][113][114][115][116][117][118][119]127]. However, at the moment there is no available consensus on the optimal duration of lamivudine therapy.…”
Section: Preemptive Use Of Nucleoside Analoguesmentioning
confidence: 99%
“…[110][111][112][113][114][115][116][117][118] Table 4 lists reports that compared patients who did and did not receive prophylactic lamivudine; all of these reports demonstrated that the prophylactic antiviral reduced HBV reactivation.…”
Section: Prevention Of Hbv Reactivationmentioning
confidence: 99%